Accounting for multiple ecosystem services in a simulation of land-use decisions: Does it reduce tropical deforestation? - Knoke, Thomas; Paul, Carola; Rammig, Anja; Gosling, Elizabeth; Hildebrandt, Patrick; Härtl, Fabian; Peters, Thorsten; Richter, Michael; Diertl, Karl-Heinz; Castro, Luz Maria; Calvas, Baltazar; Ochoa, Santiago; et al. (Global Change Biology, 2020)
Conversion of tropical forests is among the primary causes of global environmental change. The loss of their important environmental services has prompted calls to integrate ecosystem services (ES) in addition to socio-economic objectives in decision-making. To test the effect of accounting for both ES and socio-economic objectives in land-use decisions, we develop a new dynamic approach to model deforestation scenarios for tropical mountain forests. We integrate multi-objective optimization of land allocation with an innovative approach to consider uncertainty spaces for each objective. These uncertainty spaces account for potential variability among decision-makers, who may have different expectations about the future. When optimizing only socio-economic objectives, the model continues the past trend in deforestation (1975–2015) in the projected land-use allocation (2015–2070). Based on indicators for biomass production, carbon storage, climate and water regulation, and soil quality, we show that considering multiple ES in addition to the socio-economic objectives has heterogeneous effects on land-use allocation. It saves some natural forest if the natural forest share is below 38%, and can stop deforestation once the natural forest share drops below 10%. For landscapes with high shares of forest (38%–80% in our study), accounting for multiple ES under high uncertainty of their indicators may, however, accelerate deforestation. For such multifunctional landscapes, two main effects prevail: (a) accelerated expansion of diversified non-natural areas to elevate the levels of the indicators and (b) increased landscape diversification to maintain multiple ES, reducing the proportion of natural forest. Only when accounting for vascular plant species richness as an explicit objective in the optimization, deforestation was consistently reduced. Aiming for multifunctional landscapes may therefore conflict with the aim of reducing deforestation, which we can quantify here for the first time. Our findings are relevant for identifying types of landscapes where this conflict may arise and to better align respective policies.
CRIS-Team Scopus Importer:2020-02-25
Keywords: biodiversity; ecosystem services; Ecuador; land allocation; landscape restoration; robust optimization

Afforestation or intense pasturing improve the ecological and economic value of abandoned tropical farmlands - Knoke, Thomas; Bendix, Joerg; Pohle, Perdita; Hamer, Ute; Hildebrandt, Patrick; Roos, Kristin; Gerique, Andrés; Sandoval, Maria L.; Breuer, Lutz; Tischer, Alexander; Silva, Brenner; Calvas, Baltazar; et al. (Nature Communications, 2014)
Increasing demands for livelihood resources in tropical rural areas have led to progressive clearing of biodiverse natural forests. Restoration of abandoned farmlands could counter this process. However, as aims and modes of restoration differ in their ecological and socio-economic value, the assessment of achievable ecosystem functions and benefits requires holistic investigation. Here we combine the results from multidisciplinary research for a unique assessment based on a normalization of 23 ecological, economic and social indicators for four restoration options in the tropical Andes of Ecuador. A comparison of the outcomes among afforestation with native alder or exotic pine, pasture restoration with either low-input or intense management and the abandoned status quo shows that both variants of afforestation and intense pasture use improve the ecological value, but low-input pasture does not. Economic indicators favour either afforestation or intense pasturing. Both Mestizo and indigenous Saraguro settlers are more inclined to opt for afforestation.
Keywords: Agroecology; Restoration ecology

Bleiben oder Gehen? Einflussfaktoren auf die Wohnstandortmobilität anerkannter Flüchtlinge in ländlichen Räumen am Beispiel des Bayerischen Waldes - Weidinger, Tobias; Kordel, Stefan; Pohle, Perdita (Europa Regional, 2017)
Eine zunehmende Zahl von Asylbewerbern erreichte in den vergangenen Jahren Europa und wurde auf der Grundlage staatlicher Verteilungspolitiken auch in ländlichen Gebieten untergebracht. Diese Form internationaler Zuwanderung in ländliche Räume wurde in der Forschung bisher nur randständig betrachtet, wenngleich sie von unterschiedlichen Akteuren als regionaler Entwicklungsimpuls gesehen wird, mithilfe dessen sich Infrastrukturrückbau in Folge von Abwanderung und Geburtenrückgang sowie Arbeitskräftemangel entgegenwirken ließe. Es ist unklar, wie persistent diese Zuwanderungsprozesse für ländliche Räume sind und ob Asylbewerber auch nach der Zuerkennung des Flüchtlingsstatus, wenn sie ihren Wohnstandort frei wählen dürfen, auf dem Land wohnen bleiben (staying put) oder in die Städte weiterwandern (onward migration). Am Beispiel zweier Landkreise im Bayerischen Wald (Deutschland) wird im Beitrag die Wohnstandortmobilität anerkannter Flüchtlinge vor dem Hintergrund von individuellen Wohnstandortwünschen und strukturellen Faktoren wie lokalem Wohnungs- und Arbeitsmarkt, sozialem Umfeld und rechtlichen Aspekten diskutiert. Unter Zuhilfenahme des Integrationsmodells von Ager und Strang werden dabei strukturelle Spezifika ländlicher Räume für die Entscheidung über Bleiben oder Weiterwandern herausgearbeitet. Basierend auf leitfadengestützten Experteninterviews mit lokalen Akteuren zeigen empirische Daten sowohl Land-Stadt-Wanderung, Rückwanderung in ländliche Räume, Zuwanderung in ländliche Räume und rural staying. Individuelle Unsicherheitsfaktoren unterstreichen jedoch den vorläufigen Charakter der Wohnstandortmobilität anerkannter Flüchtlinge. Bei der Suche nach Wohnraum vor Ort und der Integration von Geflüchteten im sozialen Wohnumfeld kommt der Unterstützung durch lokale Akteure eine bedeutende Rolle zu, die direkt oder indirekt Einfluss auf die Wohnstandortmobilität hat. Dabei zeigen lokal-regionale Unterschiede die Heterogenität ländlicher Räum
Keywords: Migration; Mobilität; Integration; Wohnen; Flüchtlinge; ländliche Räume; Bayern

Climate Change and New Markets: Multi-Factorial Drivers of Recent Land-Use Change in The Semi-Arid Trans-Himalaya, Nepal - Meier, Wolfgang; Pohle, Perdita; Grießinger, Jussi (Land, 2022)
The Nepalese Mustang District is subject to profound environmental change. In recent decades, rising temperatures have been apparent, accompanied by increasing precipitation variability and a reduction in glacier extent. In a semi-arid climate, this reduces water availability and threatens irrigation-based subsidence agriculture. In addition, the region is experiencing rapid socio-economic change due to a new road connecting the former periphery to new markets downstream. This enables a higher market orientation for agricultural products and improved accessibility for tourists. In recent decades, these changes have triggered severe transformations in the local land-use systems and settlements, which are investigated in this study. Detailed on-site re-mappings of the settlements of Marpha and Kagbeni were performed based on historical maps from the early 1990s. Additionally, land-use patterns and functionality of buildings in the district capital of Jomsom and in the settlement Ranipauwa/Muktinath were mapped. For all settlements, a profound increase in cash crop (apple) cultivation can be observed since the 1990s. Recently, new cultivation practices such as intercropping have been extensively introduced as an adaptation strategy to climate extremes. Demand for different crops from the new markets downstream is causing a significant decline in local, well-established cultivation of traditional crops such as buckwheat. This corroborates with an increasing demand for freshwater for the enhanced vegetable cultivation used for inter-cropping. Simultaneously, the freshwater demands from the tourism sector are steadily increasing. In a region where water quality is deteriorating and springs are already drying up due to climate change, this will probably lead to further challenges regarding the allocation of water in the future.
CRIS-Team WoS Importer:2022-10-07

Confronting sustainable intensification with uncertainty and extreme values on smallholder tropical farms - Knoke, Thomas; Gosling, Elizabeth; Reith, Esther; Gerique, Andrés; Pohle, Perdita; Valle Carrion, Liz; Ochoa Moreno, Wilman Santiago; Castro, Luz Maria; Calvas, Baltazar; Hildebrandt, Patrick; Doellerer, Martin; Bastit, Felix; et al. (SUSTAIN SCI, 2022)
Sustainable intensification of agricultural lands might reconcile the conservation of tropical forest with food production, but in-depth assessments considering uncertainty and extreme values are missing. Uncertainty prohibits mapping probabilities to potential future states or ranking these states in terms of their likelihood. This in turn hampers the assessment of possible decision outcomes. Here, we use simulations to investigate how uncertainty may influence the social acceptability of alternative land-use strategies to halt tropical deforestation (including sustainable intensification), based on indicators representing farmer satisfaction. The results show how extreme values (worst values) for indicators of farmer satisfaction may undermine the adoption of sustainable intensification. We demonstrate that a pure forest conservation strategy leads to lower food production, but outperforms a sustainable intensification strategy that maintains food security. Pure forest conservation performed better, i.e., could secure higher farmer satisfaction, than sustainable intensification across a range of indicator groups. This suggests strong barriers to achieving sustainable intensification. Using agricultural subsidies breaks the dominance of pure forest conservation by enhancing the economic returns of sustainable intensification. We discuss the importance of access to labor and farmers’ preferences for the use of already cleared lands, which achieved the worst values under sustainable intensification and conclude that any assessment of land-use strategies requires careful consideration of uncertainty and extreme values.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Agricultural intensification; Farmer preferences; Land allocation; Multiple objective robust optimization; Off-farm income; Tropical deforestation

Current Provisioning Ecosystem Services for the Local Population: Landscape Transformation, Food Production, and Plant Use - Pohle, Perdita; Gerique-Zipfel, Andres; López Sandoval, María; Spohner, Regine (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Eduador, 2013)

Current provisioning services: Conservation, Management of natural Forests and Reforestation of Pastures - Weber, Michael; Stimm, Bernd; López Sandoval, María; Gerique-Zipfel, Andres; Pohle, Perdita; Hildebrandt, Patrick; Knoke, Thomas; Palomeque, Ximena; Calvas, Baltazar; Guenter, Sven; Aguirre, Nikolay; Kübler, Daniel (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)

Current Provisioning Services: Pasture Development and Use, Weeds (Bracken) and Management - Roos, Kristin; Bendix, Jörg; Curatola Fernández, Giulia; Adams, Julia; Gerique-Zipfel, Andres; Hamer, Ute; Hildebrandt, Patrick; Knoke, Thomas; Meyer, Hanna; Pohle, Perdita; Potthast, Karin; Thies, Boris; et al. (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)

Effectiveness and distributional impacts of payments for reduced carbon emissions from deforestation - Knoke, Thomas; Weber, Michael; Barkmann, Jan; Pohle, Perdita; Calvas, Baltazar; Medina, Carolina; Aguirre, Nikolay; Guenter, Sven; Stimm, Bernd; Mosandl, Reinhard; von Walter, Frank; Maza, Byron; et al. (Erdkunde, 2009)
This paper analyses the effectiveness and distributional effects of payments to avoid tropical deforestation. As a first aspect, we investigated whether or not expected payments for avoided deforestation would be acceptable for tropical farmers in Southern Ecuador, with the study area located directly adjacent to the Podocarpus National Park. Second, we explored possible distributional effects resulting from voluntary or mandatory remuneration schemes to avoid deforestation. Finally, a productive sustainable land use was conceptualised to be combined with payments for avoided deforestation to avoid leakage (i.e. deforestation processes elsewhere when avoided at a given farm). Farm level land use scenarios with ("business as usual") and without deforestation ("conservation strategy") were compared. Compensation per Mg Carbon (C) that is not emitted into the atmosphere under the "conservation strategy" was derived to achieve a monetary land net present value (NPV, sum of discounted future net revenues) equal to the NPV obtained under "business as usual". Avoided carbon emissions were computed from above ground C in tropical forests of the project area and supplemented by information on soil carbon from another study. Economic data for cattle pasturing were obtained from a farm survey (130 households) to investigate distributional effects. To derive sustainable land use concepts, a risk sensitive bioeconomic farm model was used that considered effects of risk compensation when combining pasture with reforestation of abandoned farm lands and selective logging of natural forests. The results showed that only a few farmers (20 out of 130) would possibly accept a compensation price of US 10 per Mg avoided C emission, a C-compensation that is believed by other authors to reduce deforestation by 65%. Rather a compensation of around US 25 per Mg C was necessary to address compensation requirements of farmers who hold 50% of the tropical forest area in our study. The implementation of a voluntary remuneration scheme for avoided deforestation would not introduce systematic distributional effects (such as that only the biggest farmers would benefit from compensation), while a mandatory and enforced ban on deforestation coupled with a "fair" compensation payment equal to mean compensation requirements may lead to undesirable effects for many farmers. Finally, we demonstrate a mixed sustainable land use concept that depended on cheap credits for reforestation of abandoned pasture lands. This concept was able to stop farm level deforestation and to enlarge the economic value of farms through various combined land use options (agricultural and forestry options). The combination of land uses led to risk compensatory effects and a more efficient land use by reintegrating unproductive abandoned areas back into the economical process. In our conclusion a combination of payments for avoided deforestation along with productive land use concepts provided a viable solution for tropical forest conservation.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IG.LGIPDH.effect
Keywords: Tropical forest conservation; conservation payments; carbon storage; sustainable land use

Encounters Between Experiences and Measurements: The Role of Local Knowledge in Climate Change Research - Kieslinger, Julia; Pohle, Perdita; Buitron, Viviana; Peters, Thorsten (Mountain Research and Development, 2019)
Innovative approaches could enhance scientific insights into how climate change affects mountain ecosystems and livelihoods and enrich climate action. Using an inter- and transdisciplinary approach in a remote tropical dry forest region of the Andes in southern Ecuador, this article combines local knowledge about climate change and adaptation, based on perceptions and experiences, with quantitative climate measurements. Our theoretical framework is based on the concept of vulnerability and sustainable livelihoods perspectives. Methodologically, we draw on the Participatory Rural Appraisal approach. Participatory workshops and qualitative interviews were carried out in the canton of Macara between 2015 and 2017. Local and regional climate data series were analyzed for climate trends and extreme events. Our study improves understanding of the social and physical dimension of climate change. Especially in mountain areas, differing scales of climate data must be considered to capture local climate conditions and changes. Thus, local knowledge could make a major contribution to selecting representative climate datasets, estimating local impacts of climate change, and developing adaptation policies.
CRIS-Team WoS Importer:2020-01-07

Farmers’ Preferences of Proposed Land Use Options - Pohle, Perdita; López Sandoval, María; Gerique-Zipfel, Andres (2012)

Human Ecological Dimensions in Sustainable Utilization and Conservation of Tropical Mountain Forests under Global Change - Pohle, Perdita; Gerique-Zipfel, Andres; López Sandoval, María (Biodiversity Hotspot Tropical Mountain Rainforest, 2016)

Human ecological dimensions in sustainable utilization and conservation of tropical mountain rain forests under global change in southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres; Park, Martina; López Sandoval, María (Tropical Rainforests and Agroforests under Global Change: Ecological and Socio-economic Valuations, 2010)
UnivIS-Import:2015-04-20:Pub.2010.nat.dgeo.IG.LGIPDH.humane

Indigenous concepts of land use and biodiversity conservation in southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres (Publications of the presentations on the III. Congress on the Conservation of Biodiversity of the Andes and the Amazon Region, 2005)
UnivIS-Import:2015-04-16:Pub.2005.nat.dgeo.IG.LGIPDH.indige_6

International Lifestyle Migration in the Andes of Ecuador: How Migrants from the USA Perform Privilege, Import Rurality and Evaluate Their Impact on Local Community - Kordel, Stefan; Pohle, Perdita (Sociologia Ruralis, 2016)
Using the example of Vilcabamba in Ecuador, this article explores the ways that migrants from the USA materialise their quest for better lives by relocating to smallcommunities in the Global South. Taking a lifestyle migration approach, we explore the ways migrants interpret and perform rurality in their post-migration lives according to their economic and symbolically privileged status. Empirical data gathered from biographical narrative interviews with immigrants and guideline-based interviews with experts show that migrants construct their own, mostly idealised, meanings of rurality; for instance, through the enactment of a healthy way of life close to nature, and social community spirit. Performing their privileged status through everyday practices, lifestyle migrants transfer their mostly Western understandings of rurality, derived from notions of the rural idyll, to other socio-cultural settings. Consequently, they foster various transformations of local society, economy and public space. At the same time, however, via critical self-reﬂection, they exhibit an ambivalent attitude to these transformations.
Keywords: lifestyle migration; privilege; rural idyll; rural gentrification; Ecuador

Kulturgeographisches Geländepraktikum – Handbuch und Leitfaden. - Pohle, Perdita; Kieslinger, Julia; Kordel, Stefan; Geiselhart, Klaus (2015)

Kulturgeographisches Geländepraktikum – Leitfaden. Erlanger Skripte zum Geographiestudium - Gebauer, Matthias; Geiselhart, Klaus; Fürmaier, Peter; Haferburg, Christoph; Kaplan, Lena; Kieslinger, Julia; Kordel, Stefan; Kress, Martina; Lendl, Jonas; Orlowski, Benedikt Marko; Pohle, Perdita; Schnorr, Kristina; et al. (2015)

Rechtliche und politische Rahmenbedingungen als Grundlage für sozial-ökologische Transformationen. Die Themenfelder Nachhaltigkeit, ländliche Räume, Klima- und Gewässerschutz, Biodiversität, Wald, Landwirtschaft und Energie - Pohle, Perdita; Brönner, Maximilian; Gerique-Zipfel, Andres; Kieslinger, Julia; Lederer, Lauritz (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2021)

Sitting on a ticking bomb? A political ecological analysis of conservation conflicts in the Alto Nangaritza Valley, Ecuador - Gerique-Zipfel, Andres; López Sandoval, María; Pohle, Perdita (Erde, 2017)
The Alto Nangaritza Valley in southeastern Ecuador constitutes one of the most important hotspots of biodiversity worldwide. Concerns about the exploitation of natural resources in this area have led to the creation of different types of conservation areas and policies during the last 30 years. These territorially-based conservation measures have provoked a series of conflicts between them conservation advocates and the Ecuadorian authorities on one side, and the local population who relies on the exploitation of natural resources on the other side. We analyze these conservation conflicts from a political ecological point of view, beginning with an introduction to the historical context, and then we consider the role of changing national development and spatial transformation priorities in these conflicts. Finally, in the face of the neoextractivist path that Ecuador has taken, we advocate even power relations between resource extraction and conservation policie
Keywords: Conservation; conflicts; Ecuador; Political Ecology; neoextractivism

Sustainable and Non Sustainable Use of Natural Resources by Indigenous and Local Communities - Pohle, Perdita; Gerique-Zipfel, Andres (Gradients in a Tropical Mountain Ecosystem of Ecuador, 2008)

Sustainable Livelihood in Southern Mustang District - Haffner, Willibald; Benachib, Hafida; Brock, Christoph; Gerique-Zipfel, Andres; Merl, Kerstin; Morkel, Silke; Park, Martina; Pohle, Perdita; Titz, Alexandra; Werning, Knut (Translating Development. The case of Nepal., 2003)
UnivIS-Import:2015-04-20:Pub.2003.nat.dgeo.IG.zentr.sustai

The road to integrate climate change projections with regional land-use–biodiversity models - Cabral, Juliano Sarmento; Mendoza-Ponce, Alma; da Silva, André Pinto; Oberpriller, Johannes; Mimet, Anne; Kieslinger, Julia; Berger, Thomas; Blechschmidt, Jana; Brönner, Maximilian; Classen, Alice; Fallert, Stefan; Hartig, Florian; et al. (People and Nature, 2023)
Current approaches to project spatial biodiversity responses to climate change mainly focus on the direct effects of climate on species while regarding land use and land cover as constant or prescribed by global land-use scenarios. However, local land-use decisions are often affected by climate change and biodiversity on top of socioeconomic and policy drivers. To realistically understand and predict climate impacts on biodiversity, it is, therefore, necessary to integrate both direct and indirect effects (via climate-driven land-use change) of climate change on biodiversity. In this perspective paper, we outline how biodiversity models could be better integrated with regional, climate-driven land-use models. We initially provide a short, non-exhaustive review of empirical and modelling approaches to land-use and land-cover change (LU) and biodiversity (BD) change at regional scales, which forms the base for our perspective about improved integration of LU and BD models. We consider a diversity of approaches, with a special emphasis on mechanistic models. We also look at current levels of integration and at model properties, such as scales, inputs and outputs, to further identify integration challenges and opportunities. We find that LU integration in BD models is more frequent than the other way around and has been achieved at different levels: from overlapping predictions to simultaneously coupled simulations (i.e. bidirectional effects). Of the integrated LU-BD socio-ecological models, some studies included climate change effects on LU, but the relative contribution of direct vs. indirect effects of climate change on BD remains a key research challenge. Important research avenues include concerted efforts in harmonizing spatial and temporal resolution, disentangling direct and indirect effects of climate change on biodiversity, explicitly accounting for bidirectional feedbacks, and ultimately feeding socio-ecological systems back into climate predictions. These avenues can be navigated by matching models, plugins for format and resolution conversion, and increasing the land-use forecast horizon with adequate uncertainty. Recent developments of coupled models show that such integration is achievable and can lead to novel insights into climate–land use–biodiversity relations. Read the free Plain Language Summary for this article on the Journal blog.
CRIS-Team Scopus Importer:2023-06-02
Keywords: agent-based models; biodiversity response; environmental change; indirect effects; integrative approaches; mechanistic models; socio-ecological systems; species richness

The Shuar’s Traditional Resource-Use System under Threat: Colonization Pressure in the Alto Nangaritza - Pohle, Perdita; Gerique-Zipfel, Andres; López Sandoval, María; Buitrón Cañadas, Viviana (2012)

Traditional ecological knowlegde and biodiversity management in the Andes of southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres (Geographica Helvetica, 2006)
The tropical mountain rainforests of the eastern Andean slopes in southern Ecuador have an extraordinary rich biodiversity. At the same time. these sensitive ecosystems are vulnerable because of the extension of agricultural land, the extraction of timber, mining activities, the tapping of water resources and similar anthropogenic intrusions. Ethno-specific knowledge of the tropical rainforest ecosystem was determined in sample communities of the Shuar, the Saraguros and the Mestizo-Colonos – particularly with respect to the natural forest resources and their uses. Ethnoecological and agrogeographical research methods were used to document the indigenous knowledge of traditionally utilized wild and eultivated plants, to analyze current forms of land use (including the traditional cultivation of forest and home gardens), and to evaluate ethno-specific survival strategies and strategies of biodiversity managemen
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IG.LGIPDH.tradit

Veränderungen der landwirtschaftlichen Nutzung in Bayern seit 1999. Spielt der Klimawandel eine Rolle? - Kieslinger, Julia; Brönner, Maximilian; Austermühl, Carina; Pohle, Perdita (Herausforderungen des Klimawandels in Bayern., 2021)
Vor dem Hintergrund des Klimawandels als potenzieller Einflussfaktor diskutiert der vorliegende Artikel Veränderungen in der landwirtschaftlichen Nutzung in Bayern seit 1999. Mit Hilfe einer raum-zeitlichen Sekundärdatenanalyse wird ein Überblick über Flächenentwicklungen und Erntedynamiken gegeben. Neben der Abnahme der landwirtschaftlichen Nutzfläche insgesamt, wurde bei den Dauergrünlandflächen ein bayernweiter Rückgang und bei den Ackerflächen eine Abnahme in den nördlichen/östlichen sowie eine Zunahme in den südlichen/westlichen Landkreisen deutlich. Eine Flächenzunahme ist bei Weizen, Silomais und Körnermais zu verbuchen. Die Ernteerträge lagen im Jahr 2019 bei allen Kulturpflanzen, abgesehen von Kartoffeln und Silomais, höher als im Jahr 1999. Ertragseinbußen wurden besonders in den Jahren 2003, 2013, 2015 und 2018 deutlich, die von Niederschlagsmangel, Trockenheit, überdurchschnittlich hohen Temperaturen und vielen Hitzetagen in den Sommermonaten geprägt waren. Ein Zusammenhang zwischen dem Klimawandel und der landwirtschaftlichen Nutzung in Bayern ergibt sich vor allem indirekt über klimapolitische Maßnahmen (Erneuerbare-Energien-Gesetz) und deren Folgen in den Flächenentwicklungen (Zunahme Maisanbau). Außerdem korrelieren die Ertragseinbrüche im Ackerbau mit den in den vergangenen zehn Jahren gehäuft aufgetretenen Witterungsextremen. In der landwirtschaftlichen Produktion werden Anpassungsmaßnahmen im Umgang mit Klimafolgen und Extremwetterereignissen zunehmend wichtiger.<br
Keywords: Bayern; Klimawandel; Witterungsextreme; landwirtschaftliche Nutzung; Flächenentwicklungen; Erntedynamiken

What Is Behind Land Claims? Downsizing of a Conservation Area in Southeastern Ecuador - Gerique-Zipfel, Andres; López Sandoval, María Fernanda; Pohle, Perdita (Sustainability, 2017)
Keywords: Ecuador; conservation areas; downsizing; land claims